Science Teachers’ Instructional Experiences in Learning Flexibility Modality - Geverola, Immar Jun R.; Mutya, Romel C.; Sumayao, Ernil D.; Pogoy, Angeline M. (Jurnal Penelitian dan Pembelajaran IPA, 2023)
This study aimed explore the lived experiences of science teachers’ instructions in the learning flexible modality in preparing instructions, teaching, and assessing students' learning in science. A descriptive phenomenological research design was employed with thirteen secondary science teachers who met the inclusion criteria using a purposive sampling technique. Colaizzi’s seven-step method was utilized to extract the codes, categories, and themes from the semi-structured interviews. Findings revealed three major themes: The Enthusiasm for Science Instructions, Teaching with the Spirit of Invictus, and Changeability and Rigorousness of Assessments. Science teachers face challenges in the learning flexible modality; however, their dedication and resourcefulness in teaching are the main reasons for staying on track in education. They have learned to promote inter-collegial intellectual discussions, allowing them to fill in their teaching gaps and seek improvement areas. In this study, science teachers passionately teach to support the needs of the students and cleverly update themselves with their science instructions in the flexible teaching modality. Although science teachers were able to adapt to the present changes, it is highly suggested that an avenue be provided for them to voice their concerns and make them feel that support is there from the educational sector.